COMPARATIVE AMBIENT NOISE ANALYSIS USING PROBABILITY SPECTRAL DENSITY OF BANGKA SEISMIC NETWORK - Dima Agusdiansyah; Yuliastuti Yuliastuti; Theo Alvin Ryanto; Akhmad Muktaf Haifani; Nurlaila Nurlaila (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2022)
This study analyzes the characteristics of ambient noise from four micro-earthquake observation stations located on Bangka Island nuclear power plant site. The analysis was performed using the PSD (Probability Spectral Density) method available in Obspy python-based library. Based on the observational data, the accuracy level at the four observation stations on Bangka Island is under the New High Model Noise (NHNM). Analysis was performed by comparing the 2021 and previous studies using 2014 data. An appropriate noise model as suggested by McNamara and Buland (2004) was developed using Obspy python-based library. At the period range of 0.1-1 sec, most of the station exhibits good performance. The noise level at periods 1-10 sec developed a decreasing pattern along with higher periods. At a period larger than 10 sec, 2021 data shows a better performance compared to the 2014 data.